SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) APPROACHES TO IMPROVING STUDENTS' LEARNING OUTCOMES IN THE SUBJECT OF REDOX REACTIONS - Aylinda Nurul Fadilla (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
The rapid development of science and technology affects the world of education. The challenge for 21st century educators is that teachers are required to be able to carry out innovative learning by utilizing technology to prepare students for the real world and ready to face global challenges. One approach that meets these demands is the Science, Technology, Engineering, and Mathematics (STEM) approach by applying four disciplines, namely science, technology, engineering and mathematics, as well as combining knowledge and skills. The purpose of this review is to find out the role of the STEM approach in improving student learning outcomes in the Redox Reaction chemistry subject for class XII. The method used is by collecting and reviewing data through literature studies from several relevant articles using the VOSViewer application and using the n-Gain enhancement test. The results of a review of 20 articles and 3 articles analyzed obtained data that the STEM learning approach was effective in improving student learning outcomes in Redox Reaction chemistry learning with an average increase in learning outcomes in the medium category. Through this category, learning with the Science, Technology, Engineering, and Mathematics (STEM) approach is able to improve student learning outcomes.